2015
DOI: 10.1016/j.ijpharm.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

An intravaginal ring for the sustained delivery of tenofovir disoproxil fumarate

Abstract: Recent clinical trials have demonstrated that pre-exposure prophylaxis (PrEP) may prevent HIV infection in a significant number of HIV-1 negative individuals in venerable populations; however, trial efficacy has been highly variable, with notable successes and failures. Poor adherence to PrEP regimens has been implicated as a primary factor in determining efficacy of these trials. With the exception of CAPRISA 004 where use of a pericoital tenofovir gel led to a 39% reduction in HIV infection, all successful P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…In vitro cumulative release profiles for the IVR formulation exhibited linear, sustained drug release (TDF, R 2 ϭ 0.93; MVC, R 2 ϭ 0.95), as is typical for pod-IVRs (21)(22)(23)(24)(25)27). The daily release rates obtained from the slopes of the 28-day cumulative release profiles are presented in Table 2.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In vitro cumulative release profiles for the IVR formulation exhibited linear, sustained drug release (TDF, R 2 ϭ 0.93; MVC, R 2 ϭ 0.95), as is typical for pod-IVRs (21)(22)(23)(24)(25)27). The daily release rates obtained from the slopes of the 28-day cumulative release profiles are presented in Table 2.…”
Section: Resultsmentioning
confidence: 81%
“…4A) due to various degrees of hydrolysis to TFV (27). On average, TDF made up less than 2% of the molar sum of TDF and TFV in CVL fluid samples, where both analytes were quantifiable in Ͼ95% of the samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The release rate from pod-IVRs is determined by the additive effect of the MAb solubility and three independently variable parameters: the composition and thickness of the pod's polymer membrane coating, the size and number of delivery channels through the ring exposing each individual pod to the vaginal fluid, and the number of pods in the ring. The pod-IVR design has been used for the delivery of relatively hydrophilic small-molecule antiretroviral drugs singly and in combination (43,44,48) and of ovine IgG as a model for human MAb (45). Formulation and in vitro release of VRC01-N.…”
Section: Discussionmentioning
confidence: 99%
“…Intravaginal ring (IVR) formulations of Nicotiana-manufactured VRC01 using a pod-based design (pod-IVR) (43)(44)(45) were fabricated and evaluated in vitro for release characteristics and MAb stability. Preliminary local safety and pharmacokinetics were investigated in a rhesus macaque primate model, in which it was found that steady-state vaginal fluid levels of VRC01-N were sustained over 21 days and the gp120 binding activity of the VRC01-N in the pod-IVR was retained in vivo.…”
mentioning
confidence: 99%